Industrial wastewater treatment via photo fenton - Siti Nurul Ain, Mohd Yusof (2010)
Fenton reagent has been in existence for more than 100 years, but interest in investigating the feasibility of Fenton reagent in degrading different organics is quite recent (about 20 years). The purpose of this study is to conduct experimental tests employing the Fenton oxidation process in treating the industrial detergent wastewater with the presence of UV-light. In order to achieve the objective of the research study, several scopes have been identified: to characterize and analyze the industrial detergent wastewater before and after Fenton process, to study the effect of ultraviolet exposure on Fenton process in treating industrial detergent wastewater, and to investigate the optimal process parameters (H2O2 2+dosage, Feconcentrations, optimal Fe2+/H2O2 molar ratios), and mineralization rates as well as the overall process efficiency. From the result obtained, the optimum operating condition of photo-Fenton oxidation process were involve 1500mg/L FeSO₄.7H₂O & 0.1M H₂O₂, (comply with Standard B) which COD achieve 23mg/L (98.7%) and turbidity reduction exceed 99%, optimum molar ratio more than 1 (COD removal > 94 %), X25 dilution factor (WW concentration to distilled water) and pH under 3. 1500 mg/L H₂O₂ was chosen as the best result of all the experiment. Total COD reduction of COD was up until 94%, while the turbidity reduce was 99.6%, and the color become totally clear. As conclusion, the treated wastewater is up to standard of Department of Environment Malaysia (DOE) 1974, which is comply the discharge permit of Standard B, means it is safe to be discharge to the river/downstream because it will not harm the environment, or else to undergo the next mineralization process, such as membrane filtration.